2003
DOI: 10.1074/jbc.m307493200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Sea Urchin 350-kDa Sperm-binding Protein as a New Sialic Acid-binding Lectin That Belongs to the Heat Shock Protein 110 Family

Abstract: The 350-kDa sperm-binding protein (SBP), a speciesspecific sperm-binding protein, is localized in the vitelline layer of sea urchin eggs. In this study, we have shown for the first time that sperm gangliosides are ligands for the intact glycosylated SBP. Using recombinant fragments of the SBP, the N-terminal heat shock protein 110-like domain was shown to be responsible for the binding. The intact SBP could bind various gangliosides, and the binding was sialidase-sensitive and inhibited by sialyllactose, thus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
37
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 39 publications
2
37
0
Order By: Relevance
“…It has been demonstrated that lipid rafts, isolated as low density detergent-insoluble or detergent-resistant membranes from capacitated pig sperm had high affinity for the ZP (10). Involvement of lipid rafts as platforms of cell adhesion and signaling molecules has been established earlier in fertilization (15)(16)(17), medaka fish embryogenesis (18,19), and other cellular processes (20 -23). Thus, we believe that the remodeling of lipid rafts during capacitation is of particular importance.…”
mentioning
confidence: 99%
“…It has been demonstrated that lipid rafts, isolated as low density detergent-insoluble or detergent-resistant membranes from capacitated pig sperm had high affinity for the ZP (10). Involvement of lipid rafts as platforms of cell adhesion and signaling molecules has been established earlier in fertilization (15)(16)(17), medaka fish embryogenesis (18,19), and other cellular processes (20 -23). Thus, we believe that the remodeling of lipid rafts during capacitation is of particular importance.…”
mentioning
confidence: 99%
“…Second, ESP-Sia is uniquely characterized by the presence of 9-O-sulfated Neu5Gc residues at the nonreducing termini of the α2,5O glycolyllinked oligoNeu5Gc chains. Sulfation of Sia residues might serve as a stop signal for the elongation of polySia chain as well as a protection mechanism for the polySia structure, because the sulfated Sia residues are resistant to bacterial sialidases (31,33,34). The sulfated oligoSia chains units attached to the O-linked glycan chains of SBP in the vitelline layer (81).…”
Section: α25o Glycolyl -Linked Polyneu5gcmentioning
confidence: 99%
“…Lipid rafts are characterized by the colocalization of receptor and transducer proteins, and recognized as a hot spot for signal transduction (35)(36)(37). We have shown that lipid rafts from sperm are bound by 350-kDa spermbinding protein (SBP) in the vitelline layer, during which a Sia recognition domain of SBP recognizes the Sia residues of the sperm gangliosides in the lipid rafts (31). Because sea urchin fertilization is inhibited by liposome containing the sperm ganglioside, the binding of the sperm ganglioside to SBP may be involved in interaction of sperm with the vitelline layer of the egg (31).…”
mentioning
confidence: 99%
See 2 more Smart Citations